Implementasi Pasal 9 Peraturan Walikota Bandar Lampung Nomor 43 Tahun 2021 tentang Peran Dinas Pekerjaan Umum dan Penataan Ruang Kota Bandar Lampung terhadap Perbaikan Jalan Perspektif Fiqh Siyasah Tanfidziyah : (Studi di Kelurahan Waydadi Baru Kecamatan Sukarame, Bandar Lampung) - Adinda Reza Novita; Yufi Wiyos Rini Masykuroh; Hasanuddin Muhammad (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This study evaluates the role of the Public Works and Spatial Planning Agency of Bandar Lampung City in repairing Jalan Nusa Indah Raya, Waydadi Baru Village, Sukarame District, Bandar Lampung City, based on Bandar Lampung Mayor Regulation Number 43 of 2021. The focus of the study is the implementation of Article 9 of the regulation and the review of siyāsah tanfiżiyah on the role of the Public Works and Spatial Planning Agency in road repairs. This study uses a field research method with qualitative descriptive analysis, collecting primary and secondary data. The results of the study indicate that the role of the Public Works Agency, especially the Road sector, in providing road infrastructure repair services is not optimal. This can be seen from the long-term road damage and the slow repair response. The review of siyāsah tanfiżiyah shows that the implementation of road repairs by the Public Works and Spatial Planning Agency of Bandar Lampung City is not in accordance with the applicable siyāsah tanfiżiyah principles.